Management Behavior of Online Users: Testing the Role of Financial Literacy as a Moderating Variable - Shofy, Dhiyausy Syamsi Ash; Kholilah, Kholilah (Jurnal Akuntansi Bisnis, 2024)
This research was conducted to examine the Influence of Pocket Money, Financial Self-Efficacy, Self-Control, and Religiosity on the Financial Management Behavior of Online Loan Users with Financial Literacy as a Moderation Variable. Criteria for sample selection in this study include students who are currently or have taken financial management courses at the Faculty of Economics at Universitas Islam Negeri Maulana Malik Ibrahim Malang. Data collection techniques used a questionnaire. The total sample used in this study was 106 respondents using the non-probability sampling method, namely purposive sampling. This research used a quantitative analysis approach using Partial Least Square (PLS). The results show that pocket money, self-control, and religiosity affect financial management behavior. Beside it, financial self-efficacy does not affect financial management behavior. Financial literacy does not moderate the influence of pocket money, financial self-efficacy self-control, and religiosity on financial management behavior.